A STUDY OF TYPES OF MORAL VALUES IN THE MAIN CHARACTER OF CARSTEN HENN’S NOVEL "DOOR-TO-DOOR BOOKSTORE" - Danial, Muhammad (Jurnal Review Pendidikan dan Pengajaran, 2025)
This study examines the moral values of the main character, Carl Kollhoff, in Carsten Henn’s “The Door-to-Door Bookstore”, using Linda and Richard Eyre’s theory of moral values. The analysis shows that Carl demonstrates a strong moral foundation, displaying qualities such as honesty, integrity, humility, self-awareness, understanding, potential, responsibility, and motivation. Carl also highlights generosity values, including kindness, compassion, empathy, understanding, appreciation, responsibility, consideration, and respect. These values are evident in interactions with customers, commitment to the profession, and willingness to help those in need. This research contributes to the understanding of moral values in literature by applying a specific theoretical framework and providing a detailed analysis of fictional characters. It also emphasizes the importance of ethical values in promoting a more humane and just society.